The taxonomic basis of subspecies listed as threatened and endangered under the endangered species act - Zink, Robert M.; Klicka, Luke B. (Frontiers in Conservation Science, 2022)
More than 170 subspecies are listed as threatened or endangered under the US Endangered Species Act. Most of these subspecies were described decades ago on the basis of geographical variation in morphology using relatively primitive taxonomic methods. The US Fish and Wildlife Service defaults to subspecies descriptions by taxonomists working with specific groups of organisms, but there is no single definition of subspecies across plants and animals. Valid tests today usually entail molecular analyses of variation within and among populations, although there is no reason that behavioral, ecological or molecular characters could not be used, and include tests for significant differences between samples of the putative endangered subspecies and its nearest geographic relatives. We evaluated data gathered since subspecies listed under the ESA were described finding about one-third are valid (distinct evolutionary taxa), one-third are not, and one-third have not been tested. Therefore, it should not be assumed that because a subspecies occurs in a checklist, it is taxonomically valid. If the US Fish and Wildlife Service intends to continue listing subspecies, we suggest that they convene taxonomic experts representing various groups of organisms to provide a minimal set of criteria for a subspecies to be listed under the ESA.